Improved Performance of Biohybrid Muscle‐Based Bio‐Bots Doped with Piezoelectric Boron Nitride Nanotubes. Issue 2 (4th November 2022) - Mestre, Rafael; Fuentes, Judith; Lefaix, Laura; Wang, Jiaojiao; Guix, Maria; Murillo, Gonzalo; Bashir, Rashid; Sánchez, Samuel
Abstract: Biohybrid robots, or bio‐bots, integrate living and synthetic materials following a synergistic strategy to acquire some of the unique properties of biological organisms, like adaptability or bio‐sensing, which are difficult to obtain exclusively using artificial materials. Skeletal muscle is one of the preferred candidates to power bio‐bots, enabling a wide variety of movements from walking to swimming. Conductive nanocomposites, like gold nanoparticles or graphene, can provide benefits to muscle cells by improving the scaffolds' mechanical and conductive properties. Here, boron nitride nanotubes (BNNTs), with piezoelectric properties, are integrated in muscle‐based bio‐bots and an improvement in their force output and motion speed is demonstrated. A full characterization of the BNNTs is provided, and their piezoelectric behavior with piezometer and dynamometer measurements is confirmed. It is hypothesized that the improved performance is a result of an electric field generated by the nanocomposites due to stresses produced by the cells during differentiation. This hypothesis is backed with finite element simulations supporting that this stress can generate a non‐zero electric field within the matrix. With this work, it is shown that the integration of nanocomposite into muscle‐based bio‐bots can improve their performance, paving the way toward stronger and faster bio‐hybrid robots. Abstract : Boron nitride nanotubes (BNNTs) are added to biological actuators (bio‐bots) made of skeletal muscle tissue to improve their performance. Biological and motion characterization, as well as finite element analysis simulations, demonstrate that the piezoelectric effect of these nanocomposites increases the speed of the bio‐bots and their force output.